Photoelectrochemical performance of TiO2 photoanodes: Nanotube versus nanoflake electrodes - Zhou, Xin; Denisov, Nikita; Cha, Gi; Hwang, Imgon; Schmuki, Patrik (Electrochemistry Communications, 2021)
In the present work, we compare the photoresponse of vertically erected (VE) single crystal anatase layers with that of widely used TiO2 nanotube layers. These VE-anatase layers were grown hydrothermally, directly on fluorine-doped tin oxide (FTO) glass, and consist of an array of anatase single crystal flakes with preferred (0 0 1) facets. As formed, these single crystal layers are fluorine terminated – this termination can be removed by a thermal treatment in air. We compare the photocurrent magnitude and photocurrent transients using intensity-modulated photocurrent spectroscopy (IMPS). We find that the “de-fluorinated” VE-anatase layers show significantly higher photocurrents than the comparable nanotube layers. This high efficiency of the VE-anatase layers is due to the electron transport being 100 times faster in these single crystal electrodes, provided that the blocking fluorine termination is removed.
CRIS-Team Scopus Importer:2021-02-05
Keywords: IMPS; IPCE; Photocurrent transients; TiO; VE-anatase layers